Secondary School Teachers’ Experience of Using Search Engines in Teaching and Learning - Khadka, Umesh Kumar (Creative Vision: Multidisciplinary Journal of PMC, 2025)
This research was designed to explore the secondary level teacher’s experiences of using search engines in teaching-learning activities. Twelve secondary level teachers from six different schools were selected purposively as respondents, and semi-structured interview was applied as a tool to elicit data. The research was based on a descriptive qualitative design where the collected data were transcribed, translated, coded, and analyzed following the thematic approach. The study found an increasingly ICT-friendly environment in schools as the teachers themselves managed basic ICT devices at home and schools prioritised ICT-related programs in school. The teachers used search engines to find various materials, though they were not perfect about the systematic process of searching, authenticity of materials, and ethical considerations. The majority of teachers teaching at the secondary level commonly searched and utilized instructional materials by downloading, copying, editing, and saving the source materials. As the teachers were fully positive regarding the benefits of search engines, they collaborated with colleagues and consulted different sites like YouTube to solve the problems. Basic training regarding the use of search engines seems to be mandatory, though the teachers solved various problems related to search engines by consulting with the co-workers and internet sources.